Antinuclear Antibodies With a Nucleolar Pattern Are Associated With a Significant Reduction in the Overall Survival of Patients With Leukemia: A Retrospective Cohort Study - Wang, Rong; Zhao, Huijuan; Liu, Yang; Kang, Bing; Cai, Jun (Frontiers in Oncology, 2021)
Objective: Antinuclear antibodies (ANAs) have been reported to be associated with cancers. However, the role of different ANA patterns in cancers is poorly understood, especially in leukemia. This study aimed to investigate the association between ANA patterns and the outcome of leukemia in a retrospective cohort. Methods: A total of 429 adult patients initially diagnosed with leukemia at Henan Provincial People’s Hospital from January 2014 to December 2018 were included in this study, including information on patients without positive ANAs at the time of initial diagnosis, preexisting autoimmune diseases, infectious diseases, et al. The data were retrieved up to December 2020. The final sample included 196 adult patients. The risk of death outcome according to ANA patterns was estimated using multivariable Cox proportional hazards models and the overall survival for ANA patterns was analyzed using Kaplan–Meier curve. Results: ANAs with a nucleolar pattern versus negative ANA were associated with a two-fold increased risk of death outcome in leukemia, independent of sex, age, leukemia immunophenotype, cytogenetic abnormality, treatment and blood transfusion. Further analysis revealed that the association was more significant in elder patients (≥ 60 years) and patients treated with tyrosine kinase inhibitor or chemotherapy (P for interaction = 0.042 and 0.010). Notably, the patients with a nucleolar pattern had shorter survival than the patients with a non-nucleolar pattern or without ANA (p < 0.001), Conclusion: ANAs with a nucleolar pattern are a significant predictor of poor prognosis, providing clues for prognostic assessment in patients with leukemia.